Impact of High-Velocity Oxy-Fuel ZrO2 Coating on Corrosion Resistance and Fatigue Life of AISI 316L Austenitic Stainless Steel - J. Jagadesh Kumar; G. Diwakar; Vaddi Venkata Satyanarayana (Advances in Materials Science and Engineering)
Purpose. The purpose of this research paper is to investigate the corrosion and fatigue life of AISI 316L austenitic stainless steel in the absence and presence of high-velocity oxy-fuel ZrO2 coating. Design/Methodology/Approach. AISI 316L austenitic stainless steel is chosen for the investigation, keeping in mind, its widespread usage in naval and marine applications where the members are exposed to corrosive sea water environment. ZrO2 coating is a popular surface treatment provided to mechanical members to improve their corrosion resistance. Being a refractory material, ZrO2 inhibits the corrosion of the AISI 316L austenitic stainless steel in marine applications. But, the study of the effect of ZrO2 coating on the corrosion and fatigue life of the material hitherto is scarce and hence the present investigation is undertaken. The corrosion and fatigue analysis of the coated specimens are carried out by taking two control parameters, namely, rotational speed of job and axial speed of torch, into consideration and applying L4 Taguchi orthogonal array. Findings. The corrosion resistance of the material has increased but the fatigue strength has decreased upon coating of ZrO2 on AISI 316L austenitic stainless steel. The failure has occurred because of the formation of oxide layers on the steel during coating.